2020
DOI: 10.1038/s41437-020-0317-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen, life forms, and the evolution of sexes in multicellular eukaryotes

Abstract: The evolutionary advantage of different sexual systems in multicellular eukaryotes is still not well understood, because the differentiation into male and female individuals halves offspring production compared with asexuality. Here we propose that various physiological adaptations to oxidative stress could have forged sessility versus motility, and consequently the evolution of sexual systems in multicellular animals, plants, and fungi. Photosynthesis causes substantial amounts of oxidative stress in photoaut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 140 publications
(228 reference statements)
0
10
0
Order By: Relevance
“…Although ROS are constitutive by-products of essential functions, such as respiration in mitochondria, photosynthesis, and photorespiration in chloroplasts/peroxisomes [ 33 ], their production nevertheless increases during exposure to biotic and abiotic stresses, which therefore are referred to as “oxidative stresses” [ 34 ]. In particular, the sessile nature of plants forces them to heavily rely on stress resilience strategies rather than stress avoidance [ 35 ]. Therefore, plant cells, more than animal cells, must keep steady-state levels of the various ROS under strict control, to avoid any ROS damaging effect on the macromolecules (lipids, DNA, and proteins).…”
Section: Ros and Physiological And Cellular Responses In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ROS are constitutive by-products of essential functions, such as respiration in mitochondria, photosynthesis, and photorespiration in chloroplasts/peroxisomes [ 33 ], their production nevertheless increases during exposure to biotic and abiotic stresses, which therefore are referred to as “oxidative stresses” [ 34 ]. In particular, the sessile nature of plants forces them to heavily rely on stress resilience strategies rather than stress avoidance [ 35 ]. Therefore, plant cells, more than animal cells, must keep steady-state levels of the various ROS under strict control, to avoid any ROS damaging effect on the macromolecules (lipids, DNA, and proteins).…”
Section: Ros and Physiological And Cellular Responses In Plantsmentioning
confidence: 99%
“…As a matter of fact, transcriptome analysis performed of plant female gametophyte gene expression revealed common molecular pathways affecting gamete (syngamy) and nuclear fusion (karyogamy) between those lineages [ 295 ]. Several reproductive patterns of angiosperms evolved similar to those in mammals, for instance, the embryo development surrounded by a maternal environment providing nutrients, the programmed arrest of the mature gamete before fertilization event, the presence of common parental imprinting evolved in both groups, and a selection based on male–male competition [ 35 , 296 , 297 , 298 , 299 , 300 , 301 , 302 ]. In animals, ROS is involved in sperm activation and in egg activation and fertilization [ 214 , 284 , 303 , 304 ].…”
Section: Conclusion and Future Remarksmentioning
confidence: 99%
“…[ 10 ] Horandl, Hadacek, and Speijer suggested that sex evolved in response to the massive amounts of ROS internally released by the newly acquired mitochondria. [ 11–13,67 ] A further recent theory by Tilquin, Christie, and Kokko [ 14 ] suggested that sex started with cell fusion to enable mitochondrial complementation to overcome mitochondrial decay by a mutational Muller's ratchet. Very recently Colnaghi, Lane, and Pomiankowski proposed that meiosis had to replace HGT to stop Muller's ratchet in view of the massive increase in genome size of eukaryotes.…”
Section: Sexplaining: Why Do We Need Sex?mentioning
confidence: 99%
“…These theories thus disregarded the conditions that we presently assume to have existed in early endosymbiotic eukaryotes. An exception to this are several recent hypotheses [10][11][12][13][14][15] that will be briefly described below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation